EzNav: A mobile Web browser for the elderly - Ana Mafalda Tavares Petiz dos Santos (2015)
Ageing population is increasing around the world and a similar trend is being observed in the population of Internet users. In fact, some studies revealed that people aged 60 years and over constitute the fastest growing group of information seekers on the World Wide Web. However, inadequate interface designs of existing technology tools and apps constitute a barrier to elders' digital inclusion. Besides, most older adults suffer from a decline in their visual, motor and cognitive skills that may hamper Web interaction. The project described in this document aimed at the development of an Android mobile application that consists of a Web browser for older adults, focusing on their needs. This was done through an in-depth literature review on older adults' characteristics and behaviours towards Web interaction, as well as on guidelines for designing for older people, in order to find possible modifications and improvements regarding senior user interaction with current technologies. The developed application aims at being senior-oriented, not only by considering graphical user interface (GUI) aspects (like using fewer, bigger buttons), but also Web engine aspects (removing ads, increasing spacing between paragraphs, changing colours). In order to validate the solution and get feedback from users, both low- and high-fidelity prototypes were developed and tested with a group of elders, at a day care centre. This allowed for a fast-paced cycle of continuous development and testing, thus increasing the received feedback and, consequently, the overall quality of the system. Given these premises, the development of this project followed a user-centred design (UCD) methodology, which puts the user at the centre of the design process. The results from the final usability tests proved promising, with all test participants performing all tasks, with no effort. Besides, seniors, in general, felt the application was easy to use and all of them would like to use it again, which shows great acceptance and interest in the application. Given these results, one can say that all the goals were, in general, fulfilled.